INTERNET OF THINGS BANDUNG SMART CITY - Syarif Hidayatulloh (LPPM Universitas Bina Sarana Informatika, 2016)
ABSTRACTBandung City seems so seriously in bringing the jargon of smart city. Actually, IT project in Bandung has been existed since a long time ago. Several procurements and developments of IT projects have been conducted in the previous of government era. By bringing the jargon of Bandung as “smart city”, it should be The Mayor of Bandung is trying to improve the awareness and also support from various parties related to the importance of smart city. Internet of things (Iot) is a concept that aims to expand the benefit of internet connectivity which is connected continuously. By concept internet of things (Iot) is expected become one of ideal option in the trouble of smart city application in Bandung. The scientific research of information system uses a descriptive research method by using primary data of observation result from some objects that relates to this research and also added secondary data as supporting of research objects which is reviewed by using content analysis method. The study result is obtained that Smart City Ecosystem can be achieved by implementing of smart city, but to implement it is needed a technology. One of the right choices based on reviewers of research objects which related to internet of things (Iot) technology. It needs a framework or concept to be implemented. That case is caused by many concepts, models, and hardware devices and software that are very broad scope in internet of things (Iot) technology. Therefore, the author proposes the new concept design to implement internet of things (Iot) technology for smart city in Bandung. Keywords: Smart City, Internet of Things, Smart City Ecosystem